Data Analysis from Two-choice Decision Tasks in Visual Information Processing - Kraleva, Radoslava; Kralev, Velin; Koprinkova-Hristova, Petia (JOIV : International Journal on Informatics Visualization, 2021)
Data analysis are important tasks in research. The present study focuses on the analysis of data sets from human eye movement experiments. The results of the experiments were analyzed according to two criteria – gender and age of the participants. The participants were divided into 3 groups, respectively group 1: between 20 and 35 years, group 2: between 36 and 55 years and group 3: between 56 and 85 years. The results showed that 75% of the two-choice decision tasks were solved correctly. This trend was maintained among the participants from group 1 – respectively 75.4%. The participants from group 2 gave more correct answers – respectively 82.2%, but the participants from group 3 gave fewer correct answers – respectively 70.2%. The average value of the response time indicator (of all participants) was 1455 ms. The response time of the participants from groups 1 and 2 was shorter than the average (respectively with 483 ms and 235 ms). The response time of the participants from group 3 was longer than the average (respectively with 626 ms).